Reliability of the Multiplex CytoBead CeliAK Immunoassay to Assess Anti-tTG IgA for Celiac Disease Screening - Abdukhakimova, Diyora; Dossybayeva, Kuanysh; Grechka, Anna; Almukhamedova, Zhaina; Boltanova, Alyona; Kozina, Larissa; Nurgaliyeva, Kadisha; Hasanova, Liliya; Tanko, Matthew N.; Poddighe, Dimitri (Frontiers in Medicine, 2021)
Background and objective: The diagnosis of Celiac Disease is first based on the positivity for specific serological markers. The CytoBead CeliAK immunoassay simultaneously measures antibodies (IgA) directed to anti-tissue transglutaminase (tTG), anti-endomysium (EMA), and deamidated gliadin (DG), in addition to provide a control for normal total IgA levels. The aim of this study is to assess the reliability of this multiplex assay to detect anti-tTG antibody positive patients, compared to a conventional single-parameter ELISA. Methods: Serum samples from 149 pediatric patients were assessed by both CytoBead CeliAK immunoassay and ELISA, in order to evaluate their concordance for the measurement of anti-tTG IgA. Results: The measurement of anti-tTG IgA by CytoBead CeliAK immunoassay basically showed a concordance rate of 100% between the conventional and single-parameter ELISA, according to the respective cut-off values (3 U/ml and 10 U/ml). Conclusions: Our comparative analysis first demonstrates a substantial equivalency between multiplex CytoBead CeliAK assay and the single-parameter conventional ELISA to assess the anti-tTG IgA antibody in the context of the screening for CD. Importantly, CytoBead CeliAK assay presents some pre-analytic, analytic, and economic advantages.